(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Internet Addictionis a significant emerging mental health condition among Indian college students and cascading into a major public health concern. Internet addiction has witnessed an upsurge as a clinical phenomenon among young adults precipitated by new challenges specific to this developmental age and owing to its complexity resulting from multiple psychosocial factors which warrants the need for effective multi modal intervention due to high relapse rates and resistance to treatment. Aim: The present investigation was aimed to evaluate the association of Internet Addiction with social support, loneliness and stress among female college students in Chandigarh. Methodology: It was a cross sectional study among 200 undergraduate female students within the age range of 18-21 years, drawn from various colleges pertaining to Chandigarh region. Internet Addiction Test (Young, 1998) was employed as a screening instrument to identify internet dependence and other assessment tools administered include Perceived Stress Scale, Multidimensional Perceived Social Support scale and UCLA Loneliness Scale. Results: Comparative Analysis revealed that there were significant differences between Internet Addiction and Non Internet Addiction groups of female college students in the areas of Stress, Loneliness and Family Support. Bivariate correlation analysis showed a positive relationship of Internet Addiction with Stress and Loneliness. However there emerged a negative correlation between Internet Addiction and Family Support. Conclusion: Our study holds heuristic value for elucidating the potential impact of low family support and heightened stress due to plethora of reasons may increase vulnerability to Internet Addiction among female college students. We can conclude that young adults with insufficient or conflictual family interaction triggers emotional loneliness resulting in either social withdrawal or search for needed relationships in the Internet environment. Hence, family support is an important factor in treating and preventing Internet addiction.